1986
DOI: 10.1620/tjem.148.151
|View full text |Cite
|
Sign up to set email alerts
|

The dopaminergic regulation of plasma growth hormone secretion in normal subjects.

Abstract: The role of endogenous dopamine (DA) on plasma GH secretion was studied using domperidone (DA receptor blocker which does not cross blood brain barrier) in 16 normal subjects. After a bolus injection of domperidone (10 mg, iv.), plasma PRL in 11 cases rose quickly and markedly from the basal level of 9.5+ 1.2 ng/ml (Mean+s.E.) to a maximum of 76.3+ 10.6 ng/ml at 30 min. In contrast, plasma GH in these cases showed a delayed and slight increases to domperidone injection where the values at 90 min and 120 min (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Dopaminergic influences on the lactotrophic system are inhibitory: basal prolactin concentrations are suppressed by DA, dopaminergic agonists and l ‐dopa in healthy individuals (14–22) and in patients with IPD (3, 10, 23–25). Dopaminergic agonists are able to abolish the TRH‐induced prolactin rise (24, 26, 27), which also might be diminished due to IPD itself (5).…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic influences on the lactotrophic system are inhibitory: basal prolactin concentrations are suppressed by DA, dopaminergic agonists and l ‐dopa in healthy individuals (14–22) and in patients with IPD (3, 10, 23–25). Dopaminergic agonists are able to abolish the TRH‐induced prolactin rise (24, 26, 27), which also might be diminished due to IPD itself (5).…”
Section: Discussionmentioning
confidence: 99%
“…The oral administration of L‐dopa alone (Mars & Genuth ; Hanew et al . ), an AADC inhibitor (MK‐486) plus L‐dopa (Mars & Genuth ) and carbi plus L‐dopa (Bansal et al . ) was shown to increase basal plasma GH concentrations in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The oral administration of L-dopa alone (Mars & Genuth 1973;Hanew et al 1986), an AADC inhibitor (MK-486) plus L-dopa (Mars & Genuth 1973) and carbi plus L-dopa (Bansal et al 1981) was shown to increase basal plasma GH concentrations in humans. In these studies, the GH peaks induced by L-dopa appeared 60-90 min after its administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations